2019
DOI: 10.3390/ijms20102382
|View full text |Cite|
|
Sign up to set email alerts
|

Doratoxylon apetalum, an Indigenous Medicinal Plant from Mascarene Islands, Is a Potent Inhibitor of Zika and Dengue Virus Infection in Human Cells

Abstract: Zika virus (ZIKV) and Dengue virus (DENV) are mosquito-borne viruses of the Flavivirus genus that could cause congenital microcephaly and hemorrhage, respectively, in humans, and thus present a risk to global public health. A preventive vaccine against ZIKV remains unavailable, and no specific antiviral drugs against ZIKV and DENV are licensed. Medicinal plants may be a source of natural antiviral drugs which mostly target viral entry. In this study, we evaluate the antiviral activity of Doratoxylum apetalum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 48 publications
0
33
0
1
Order By: Relevance
“…The treatments were able to prevent infection of both strains of ZIKV in trophoblast cells (A, B and D). Experiments were performed in n = 6. from Mascarene Island, which inhibited Zika and Dengue virus infection in leukocytes (Haddad et al, 2019). One polyphenol present in large amounts in the green tea, (−)-epigallocatechin gallate (EGCG), has been also described as a potent antiviral molecule, able to inhibit ZIKV entry in Vero E6 cells (Carneiro et al, 2016).…”
Section: Flow Cytometry Analysis On Zikv Infection Of Htr-8/svneo Cellsmentioning
confidence: 99%
“…The treatments were able to prevent infection of both strains of ZIKV in trophoblast cells (A, B and D). Experiments were performed in n = 6. from Mascarene Island, which inhibited Zika and Dengue virus infection in leukocytes (Haddad et al, 2019). One polyphenol present in large amounts in the green tea, (−)-epigallocatechin gallate (EGCG), has been also described as a potent antiviral molecule, able to inhibit ZIKV entry in Vero E6 cells (Carneiro et al, 2016).…”
Section: Flow Cytometry Analysis On Zikv Infection Of Htr-8/svneo Cellsmentioning
confidence: 99%
“…The current search for ZIKV antiviral options is being conducted through several different approaches which target different steps of the replication cycle: by screening of different compound libraries or by the repurposing of drugs with known active efficacy against other diseases and that are already being used in clinic. In addition, natural products [40,41] as well as antibody-based candidates [42,43] are being evaluated but are outside the scope of this review. Antivirals can be classified according to their mode of action in (i) direct-acting antivirals, directed against viral targets, or (ii) host-targeting antivirals, aimed at targeting cellular components needed for the viral cycle.…”
Section: Potential Therapeutic Options For the Treatment Of Zikv Imentioning
confidence: 99%
“…Many of the indigenous and endemic plants from Reunion island have been and are still used for traditional medicine [ 3 ]. Although some studies have reported the potential therapeutic effects of these plants in combatting hypertension [ 4 ], oxidative stress, inflammation [ 5 ], parasitosis (i.e., plasmodium), and viruses (i.e., Chikungunya, Dengue, and Zika) [ 6 , 7 , 8 ], their deep content characterization as well as their real efficiency in vivo remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%